The Traps of [Lacking]Memory. Representations of the GULag in the 21st Century Culture: Literature, Film, and Art - Artwińska , Anna (Poznańskie Studia Slawistyczne, 2020)
The subject of the article is the review of the book “Inwiefern ist das heute inter-essant?” Erinnerungen an den stalinistischen Gulag im 21. Jahrhundert by the German literary scholar Nina Friess (2016), which is dealing with the contemporary Russian memory of the Gulag. The goal is to show how the author interprets and contextualizes memory practices in today’s Russia and which texts are crucial for her as manifestations of these remembering strategies (and forgetting as well). Reading this book allows to form the thesis that the extreme experience of the Soviet camps is still a controversial issue in the Russian culture and that the memory of it is full of gaps and empty spaces, even though at the same time this subject increasinly finds its way into popular cultural (graphic novels and crime thrillers).